2022
DOI: 10.21608/jampr.2022.130700.1026
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Staphylococcus aureus and Methicillin-resistant S. aureus (MRSA) in Ear Infections in Tanta, Egypt

Abstract: Ear infection is a common clinical problem worldwide and the main cause of preventable hearing loss in the developing world. The increasing incidence of methicillin-resistant Staphylococcus aureus infections (MRSA) in ear, nose and throat (ENT) diseases is becoming a big clinical concern. This study aimed to investigate Staphyloccocus aureus (S. aureus) as a common bacterial causative agent of ear infection, characterize the isolates resistance profiles, investigate the incidence of MRSA among S. aureus isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
2
1
Order By: Relevance
“…Our results were at conflicts with a research by Sonbol et al [ 35 ], which revealed that ciprofloxacin had the lowest resistance rates (3.7% resistance) against the tested isolates. Additionally, substantial resistance rates to rifampin (57.4%) were found, which was higher than our findings for rifampin, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results were at conflicts with a research by Sonbol et al [ 35 ], which revealed that ciprofloxacin had the lowest resistance rates (3.7% resistance) against the tested isolates. Additionally, substantial resistance rates to rifampin (57.4%) were found, which was higher than our findings for rifampin, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…2 Staphylococcus aureus is considered one of the predominant bacterial causes of ear infections and shows a global concern in resistance to the most available treatment options. 20 Nowadays, the emergence of MRSA isolates is becoming a growing challenge as it can impair the management of Staphylococcus aureus infections. 20 World Health Organization (WHO) has reported that 64% of people with MRSA infections are more likely to die than people with drug-sensitive infections.…”
Section: Discussionmentioning
confidence: 99%
“…20 Nowadays, the emergence of MRSA isolates is becoming a growing challenge as it can impair the management of Staphylococcus aureus infections. 20 World Health Organization (WHO) has reported that 64% of people with MRSA infections are more likely to die than people with drug-sensitive infections. 21 The study reveals more than fifty percent of Staphylococcus aureus isolates were MRSA.…”
Section: Discussionmentioning
confidence: 99%